O retrato da mulher preta em estudos da Ciência da Informação no Brasil - Pereira, Gabriele Rodrigues (2021)
This research surveys studies on black women in Brazilian science, more specifically in Information Science. Recognizing academic production about black women in Information Science means removing them from the spaces of servitude attributed to the colonial period, in the process of enslavement, and giving black women a prominence as producers of their own knowledge. During the research, it is questioned how black women have been studied in Information Science in Brazil. The research in the context of Information Science is justified because it involves aspects of the organization and representation of information, which corroborates the definition of an overview of how the theme has been discussed in the area, as well as to support discussions on the protagonism of black woman in Information Science and give visibility to her struggles against the erasure of African knowledge. Therefore, it was defined as a general objective to discuss studies on black women in Information Science in Brazil. The research, of an applied nature, adopts a qualitative approach using literature mapping as part of bibliographic procedures and uses content analysis in data analysis. The results indicate that subjects such as Black Feminism, Black Woman Protagonism, Female Empowerment, Black Identity, Black Woman Representation, Ethnic-racial Information, Afro-Brazilian Culture, Quilombola Community and African-Made Religion emphasize black women.